"Water for everything, but not for everyone." An educational experience in the area of Social Sciences in times of pandemic. - Jara Gómez, Katherine Geraldine (2021)
A pedagogical experience used the strategies of Project Based Learning and Collaborative Learning in​​Social Sciences. It was promoted, among the fifth-year high school students of a private institution in North Lima; the planning, preparation and dissemination of virtual propaganda, on the responsible use of water in the framework of the Covid-19 pandemic. This project generated an active role for students in the learning-teaching process, and research, autonomous learning and other competencies stipulated in the National Basic Education Curriculum (CNEB) were also stimulated.